Dysregulation of sphingolipid metabolic enzymes leads to high levels of sphingosine‐1‐phosphate and ceramide in human hepatocellular carcinoma. Issue 5 (9th March 2021) - Miura, Kohei; Nagahashi, Masayuki; Prasoon, Pankaj; Hirose, Yuki; Kobayashi, Takashi; Sakata, Jun; Abe, Manabu; Sakimura, Kenji; Matsuda, Yasunobu; Butash, Ali L.; Katsuta, Eriko; Takabe, Kazuaki; et al.
Abstract: Aim: Sphingosine‐1‐phosphate (S1P) and ceramide are bioactive sphingolipids known to be important in regulating numerous processes involved in cancer progression. The aim of this study was to determine the absolute levels of sphingolipids in hepatocellular carcinoma (HCC) utilizing data obtained from surgical specimens. In addition, we explored the clinical significance of S1P in patients with HCC and the biological role of S1P in HCC cells. Methods: Tumors and normal liver tissues were collected from 20 patients with HCC, and sphingolipids were measured by mass spectrometry. The Cancer Genome Atlas (TCGA) cohort was utilized to evaluate gene expression of enzymes related to sphingolipid metabolism. Immunohistochemistry of phospho‐sphingosine kinase 1 (SphK1), an S1P‐producing enzyme, was performed for 61 surgical specimens. CRISPR/Cas9‐mediated SphK1 knockout cells were used to examine HCC cell biology. Results: S1P levels were substantially higher in HCC tissue compared with normal liver tissue. Levels of other sphingolipids upstream of S1P in the metabolic cascade, such as sphingomyelin, monohexosylceramide and ceramide, were also considerably higher in HCC tissue. Enzymes involved in generating S1P and its precursor, ceramide, were found in higher levels in HCC compared with normal liver tissue. Immunohistochemical analysis found that phospho‐SphK1 expression was associated with tumor size. Finally, in vitro assays indicated that S1P is involved in the aggressiveness of HCC cells. Conclusions: Sphingolipid levels, including S1P and ceramide, were elevated in HCC compared with surrounding normal liver tissue. Our findings suggest S1P plays an important role in HCC tumor progression, and further examination is warranted.